2000
DOI: 10.1152/ajprenal.2000.279.5.f910
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin attenuates acute renal failure and oxidative stress induced by mercuric chloride in rats

Abstract: We evaluated the effect of melatonin (Mel), a potent scavenger of reactive oxygen species, in the course of HgCl(2)-induced acute renal failure. Rats received by gastric gavage 1 mg/kg of Mel (n = 21) or vehicle (n = 21), 30 min before the subcutaneous injection of HgCl(2) (2.5 mg/kg). Rats were killed at 24, 48, and 72 h, and plasma creatinine (S(cr)), renal histology, proliferative activity, apoptosis, and superoxide-producing cells were studied. We also determined the renal content of malondialdehyde (MDA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
65
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 47 publications
(55 reference statements)
12
65
0
Order By: Relevance
“…35 Another important inflammatory cytokine, IL-6, exhibits many physiological effects. 36 Contrast media administration was shown to lead to an increase in the levels of IL-6 in the kidney, 38 while TNF-a led to an increase in NF-kB. 51,52 In our study, NF-kB upregulation, in parallel with contrast media and glycerol administration, correlated with the increasing levels of TNF-a and IL-6.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…35 Another important inflammatory cytokine, IL-6, exhibits many physiological effects. 36 Contrast media administration was shown to lead to an increase in the levels of IL-6 in the kidney, 38 while TNF-a led to an increase in NF-kB. 51,52 In our study, NF-kB upregulation, in parallel with contrast media and glycerol administration, correlated with the increasing levels of TNF-a and IL-6.…”
Section: Discussionsupporting
confidence: 55%
“…The latest literature states that melatonin averts nephrotoxicity triggered by several drugs. [33][34][35][36][37][38] In particular, Gazi et al 39 demonstrated the defensive effect of melatonin administration in rat radiocontrast nephrotoxicity by reducing BUN and creatinine levels. 40 However, these studies have not measured oxidative and molecular parameters to indicate whether regeneration of the kidneys occurred after injury.…”
Section: Discussionmentioning
confidence: 99%
“…[13] In addition to those using sepsis models, other studies have demonstrated beneficial effects of melatonin on renal damage as ischemia-reperfusion injury or acute renal failure. [11,18,36] Agomelatine has generally been studied in relation to depressive and anxiety disorders, and, to the best of our knowledge, the present study is the first to research its effects on sepsis-related AKI. Agomelatine has effects similar to those of melatonin, due to its melatonergic receptors.…”
Section: Discussionmentioning
confidence: 85%
“…[14] In addition, reports have indicated protective effects of melatonin on renal functions. [17][18][19] However, exact pathophysiology of sepsisrelated AKI remains unclear and, in spite of new treatment options, AKI continues to occur with high mortality. [20] The aim of the present study was to research effects of agomelatine, a melatonin analogue, on sepsis-induced AKI.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors show an anti-apoptotic action of melatonin in different organs, such as thymus, kidney, brain and liver, attributing this mainly to its antioxidating properties [7][8][9][10][11][12]33,34 when eliminating radicals hydroxyl (OH -), peroxyl (ROO -) 26, superoxides 4 and cardiolipin oxidation from mitochondrias 35 . In the lacrimal glands of hamsters, this hormone prevents cell damage caused by the buildup of porphyrins, due to its capacity of decreasing the RNAm synthesis of aminolevulinate synthetase, enzyme involved in the production of porphyrins, and also due to increasing the levels of RNAm of antioxidating enzymes such as manganese superoxide dismutase (Mn-SOD) and copper-zinc superoxide dismutase (Cu-Zn-SOD) 36 .…”
Section: Melatonin Action In Apoptosismentioning
confidence: 99%